PERSUASION IN TOURISM PROMOTION BILINGUAL TEXTS: THE IMPORTANCE OF SYNTACTIC FORMS AND CHOICES - Bayu Budiharjo; Ardianna Nuraeni; Nur Saptaningsih; Bayu Dewa Murti; Anita Rusjayanti (UIN Raden Mas Said Surakarta, 2022)
This study is aimed at examining the message communicated by verbal material in bahasa Indonesia and English in the Boyolali tourism promotion bilingual booklet. The study employs descriptive qualitative approach and applies qualitative data analysis under the framework of Syntax. The research data take form of sentences in the Boyolali tourism promotion bilingual booklet in bahasa Indonesia and in English. The findings show that Boyolali tourism promotion bilingual booklet carries an inequivalent message in terms of informative content and persuasive force. This research has also proven that syntax is a substantial asset in the formation of promotional messages in the promotion of tourism destinations of Boyolali.